Motion Sickness Manifestations and Prevention - Kumar, G. P.; Anilakumar, K. R.; Sekhar, Y. C.; Sharma, Rakesh Kumar (Defence Life Science Journal, 2020)
Motion sickness is an ancient problem associated with transportation (ships and other vehicles), which is affecting humans since ages. Motion sickness is characteristically occurring during abnormal movements induced by the motion and when there is a conflict between various senses such as visual, vestibular and motor system. Depending on the type of motion, various kinds of sicknesses, such as air sickness, car sickness, train sickness, seasickness, etc. may occur. A very less per cent of individuals are highly susceptible to motion sickness and very less per cent of individuals are highly insusceptible for motion sickness. However, most of the population comes in between. The primary symptoms of motion sickness include nausea, vomiting, wanes, and cold sweating. Varieties of drugs are available to reduce susceptibility to motion sickness. However, nausea, pallor, sweating, headache, dizziness, malaise, increased salivation, apathy, drowsiness, belching, hyperventilation and stomach awareness are the other symptoms of motion sickness. Anti-cholinergics and anti-histamines are the most effective motion sickness prophylactics with apparent side effects such as dry mouth, drowsiness, and depression. There are theories and mechanisms which include intra-vestibular (Canal-Otolith) mismatch theory, sensory conflict theory, visual-vestibular mismatch theory, the poison theory, the postural instability theory, and the movement program theory. Benzodiazepines, anticholinergics, anti-histamines and monoamine antagonists have commonly used treatment regimes. The traditional way of tackling the problem is the consumption of ginger, peppermint, lemon, fennel, marjoram, rosemary, basil. This review summarizes prediction and evaluation, behavioural strategies to prevent or minimize symptoms of motion sickness and available countermeasures of motion sickness.